Quantification of breast stiffness using MR elastography at 3 Tesla with a soft sternal driver: A reproducibility study. Issue 5 (25th October 2016) - Hawley, Jeffrey R.; Kalra, Prateek; Mo, Xiaokui; Raterman, Brian; Yee, Lisa D.; Kolipaka, Arunark
Abstract : Purpose: Previous studies of breast MR elastography (MRE) evaluated the technique at magnetic field strengths of 1.5 Tesla (T) with the breast in contact with the driver. The aim of this study is to evaluate breast stiffness measurements and their reproducibility using a soft sternal driver at 3T and compare the results with qualitative measures of breast density. Materials and Methods: Twenty‐two healthy volunteers each underwent two separate breast MRE scans in a 3T MRI. MRE vibrations were introduced into the breasts at 60 Hz using a soft sternal driver and axial slices were collected using a gradient echo MRE sequence. Mean stiffness measurements were calculated for each volunteer as well as a measure of reproducibility using concordance correlation between scans. Mean stiffness values for each volunteer were assessed and related to amounts of fibroglandular tissue (i.e., breast lobules, ducts, and fibrous connective tissue). Results: The stiffness values were reproducible with a significant P ‐value < 0.0001 between two scans with concordance correlation of 0.87 and 0.91 for center slice and grouping all slices, respectively. Volunteers with dense breasts (i.e., higher grades of fibroglandular tissue) had mean stiffness values of 0.96 kPa (center slice) and 0.92 kPa (all slices) while those without dense breasts had mean stiffness values of 0.85 kPa (center slice) and 0.83 kPa (all slices) ( P  ≤ 0.05). Conclusion: Breast MRE is a reproducible technique at 3T using a soft sternal driver. Dense breasts had significantly higher stiffness measurements compared with nondense breasts. Level of Evidence : 2 J. MAGN. RESON. IMAGING 2017;45:1379–1384